Does Firm Size Matter? A Moderated Analysis of Profitability and Liquidity Effects on Stock Price - Gunawan, Maulidyana Putria; Herawati, Heti (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
This study aimed to examine the effect of profitability and liquidity on stock prices, with firm size as a moderating variable, in primary consumer goods companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Using a purposive sampling method, a total of 395 samples were selected. Data were processed using EViews 12 software, and Moderated Regression Analysis (MRA) was employed to analyze the relationships among variables. The results indicate that profitability has no significant effect on stock prices, liquidity has a negative effect on stock prices, and firm size does not moderate the relationship between profitability and stock prices but does significantly moderate the relationship between liquidity and stock prices